Experimental study and numerical simulation of dynamic recrystallization behavior of TiAl-based alloy. (15th May 2017) - Wan, Zhipeng; Sun, Yu; Hu, Lianxi; Yu, Huan
Abstract: An Avrami-type equation was used to investigate the dynamic recrystallization (DRX) behavior of a TiAl-based alloy during hot compression tests. The effects of hot deformation parameters on DRX behavior of samples were determined based on the established dynamic recrystallization kinetics model. The nucleation mechanism of dynamic recrystallization and the microstructure evolution of the deformed samples were studied using electron backscatter diffraction (EBSD). Discontinuous dynamic recrystallization (DDRX) is subsequently identified by obvious nucleation and grain growth. It was indicated that the DRX volume fraction and grain size decrease with the decrease of deformation temperature or the increase of strain rate. The TEM images show that the deformation twinning of γ-phase is formed during hot deformation which can provide more nucleation sites for DDRX and promote the occurrence of DRX significantly. Furthermore, the determined kinetics model was programmed into finite element codes to investigate the DRX behavior of the TiAl-based alloy during hot deformation. The equivalent strain distribution and DRX volume fraction evolution calculated by simulated approach can well demonstrate the experiment results. Graphical abstract: Highlights: Dynamic recrystallization behavior is investigated based on experimental and simulated analysis. Discontinuous dynamic recrystallization nucleation mechanism is identified. Critical conditions are determined and mean critical strain ratio ( ε c /ε p ) is 0.73. Established model and numerical simulation show excellent predictive capability.